PERAN MEDIA FLASH CARDS UNTUK PENGENALAN KEMAMPUAN BAHASA INGGRIS ANAK USIA 5-6 TAHUN DI PAUD AISHA KOTA MATARAM - Ulimah, Putri; Habibi, Muazar; Astini, Baik Nilawati (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2018)
This study aims to determine the role of flash cards media for the introduction of English language skills of children aged 5-6 years at PAUD Aisha Mataram in the 2016/2017 academic year. The study was conducted using an experimental approach, and with a comparative quantitative research method. The population in this study were all students aged 5-6 years at PAUD Aisha Mataram. The sampling technique used was saturated sampling, by making the entire population a sample so that 12 students were obtained. Data collection techniques were obtained with guided observation instruments. The instrument trial consisted of validity tests and reliability tests. The prerequisite analysis test used in this study used the Wilcoxon Match Pairs Test using a helper table of levels and hypothesis testing by comparing the calculated t price with the Wilcoxon t table. The results of this study were that the pre-test data collected obtained an average score of 31.17 after being given treatment, the post-test data obtained became 45.67. The results of the hypothesis test show the value of t count = 0.0 while t table with N = 12 at a significance level of 5% (0.05) is 14 so that t count <t table (0.0 <14), Ho is rejected. It can be concluded that there is a role of flash cards media for the introduction of English language skills for children aged 5-6 years at PAUD Aisha Mataram in the 2016/2017 academic year. The suggestion from this study, one way to optimize children's English language skills can be done by improving the quality and type of media used in learning, so that children's interest in learning English increases.